MR and CT Imaging for the Evaluation of Pulmonary Hypertension - Freed, Benjamin H.; Collins, Jeremy D.; François, Christopher J.; Barker, Alex J.; Cuttica, Michael J.; Chesler, Naomi C.; Markl, Michael; Shah, Sanjiv J. (JACC. Cardiovascular imaging, 2016)
Imaging plays a central role in the diagnosis and management of all forms of pulmonary hypertension (PH). Although Doppler echocardiography is essential for the evaluation of PH, its ability to optimally evaluate the right ventricle and pulmonary vasculature is limited by its 2-dimensional planar capabilities. Magnetic resonance and computed tomography are capable of determining the etiology and pathophysiology of PH, and can be very useful in the management of these patients. Exciting new techniques such as right ventricle tissue characterization with T1 mapping, 4-dimensional flow of the right ventricle and pulmonary arteries, and computed tomography lung perfusion imaging are paving the way for a new era of imaging in PH. These imaging modalities complement echocardiography and invasive hemodynamic testing and may be useful as surrogate endpoints for early phase PH clinical trials. Here we discuss the role of magnetic resonance imaging and computed tomography in the diagnosis and management of PH, including current uses and novel research applications, and we discuss the role of value-based imaging in PH.